FORMATION OF ENGLISH AND UZBEK MUSICAL LEXICAL UNITS UNDER THE INFLUENCE OF EUROPEAN AND EASTERN CULTURE (SCIENCE TIME JOURNAL, 2026)
This article explores the formation of musical lexical units in English and Uzbek languages, examining how European and Eastern cultural influences have shaped their terminology. Drawing on historical, linguistic, and ethnomusicological perspectives, it analyzes the etymology, semantics, and comparative aspects of key terms. English musical lexicon is predominantly influenced by European languages like Italian, French, and German, reflecting the dominance of Western classical traditions, while Uzbek terms draw from Eastern sources such as Persian, Arabic, and Turkish, with later European overlays via Russian colonialism. Through a comparative methodology, the study highlights similarities in borrowing processes and differences rooted in cultural contexts. It discusses implications for cross-cultural understanding and linguistic evolution in music. The analysis is supported by real scholarly sources, emphasizing the interplay between culture and language in musical expression.